1993
DOI: 10.1071/ch9930693
|View full text |Cite
|
Sign up to set email alerts
|

Collision-Induced Dissociations of Deprotonated Peptides. Dipeptides Containing Asn, Arg and Lys

Abstract: The presence and position of Asn, Arg and Lys residues in dipeptides may be determined from a consideration of the collisional activation mass spectra of the (M-H)- ions formed by fast atom bombardment. All spectra show the basic dipeptide cleavage, i.e. NH2CH(R1)CONHCH(R2)CO2- → NH2C(R1)CONHCH(R2)CO2H → NH2C(R1)=C=O + -NHCH(R2)CO2H. There are a number of fragmentations characteristic of a particular α side chain: for example, Arg loses HN=C=NH (42 u).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…A comparison of the low-energy CID results with the high-energy CID results reported by Eckersley et al [12] showed that more extensive and sequence-specific fragmentation was observed in the low-energy CID experiments. This observation is in line with earlier work in this laboratory [20 -23] which showed that low-energy collisional activation of negative ions imparted, on average, greater energy to the anion than did high-energy collisional activationThe early studies [7][8][9][10][11][12][13][14][15][16][17][18] …”
supporting
confidence: 81%
See 1 more Smart Citation
“…A comparison of the low-energy CID results with the high-energy CID results reported by Eckersley et al [12] showed that more extensive and sequence-specific fragmentation was observed in the low-energy CID experiments. This observation is in line with earlier work in this laboratory [20 -23] which showed that low-energy collisional activation of negative ions imparted, on average, greater energy to the anion than did high-energy collisional activationThe early studies [7][8][9][10][11][12][13][14][15][16][17][18] …”
supporting
confidence: 81%
“…On the other hand much less is known concerning the fragmentation modes of deprotonated peptides. The majority of studies [7][8][9][10][11][12][13][14][15][16][17][18] have involved high-energy collision-induced dissociation (CID) and have been largely restricted to the [M Ϫ H] Ϫ ions of dipeptides with only a few tripeptides having been studied.A recent paper from this laboratory [19] has reported the low-energy CID of the [M Ϫ H] Ϫ ions of a variety of dipeptides to pentapeptides containing H or alkyl ␣-groups. The fragmentation reactions observed are illustrated schematically in Scheme 1 using nomenclature adapted from that used [6,7] for fragmentation of protonated peptides.…”
mentioning
confidence: 99%
“…In addition, abundant c 4 − is produced although its intensity is generally lower than that of [M − H − NH 3 ] − and [M − H −42] − . Loss of NHCNH from arginine residues in deprotonated peptides has previously been observed by high‐energy CID24 and PSD 22. In addition, no preferential cleavage occurs adjacent to the arginine; this residue does not influence the dissociation pathways of [M − H] − .…”
Section: Resultsmentioning
confidence: 59%
“…However, the peptides in the PSD study generally had many types of residues, making it difficult to elucidate how the basic residues themselves were affecting fragmentation. In addition, Bowie and coworkers23, 24 have shown that b‐ and y‐ions are primarily produced from high‐energy collision‐induced dissociation (CID) of small deprotonated peptides containing histidine, lysine and arginine. Interestingly, these spectra did not contain the c n − series that was seen by PSD 22…”
Section: Introductionmentioning
confidence: 99%
“…Another example of side chain deprotonation was observed by Grzetic and Oomens via IRMPD 33 as well as Bowie and co-workers by CID on asparagine-containing peptides. 10,34 Both groups proposed a succinamide structure that deprotonates at the asparagine side chain and allows charge-directed backbone cleavage.…”
Section: ■ Introductionmentioning
confidence: 99%